PENGGUNAAN METAFORA DALAM KUMPULAN PUISI “SEBELUM SENDIRI” KARYA M. AAN MANSYUR: THE USE OF METAPHOR IN THE POETRY COLLECTION ‘SEBELUM SENDIRI’ BY M. AAN MANSYUR - Safhira, Alma Nur; Hamsa, Akmal; Agussalim AJ, Andi (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
The purpose of this research is to describe the forms, meanings, and functions of metaphors in the poetry collection 'Before Alone' by M. Aan Mansyur. The data in this study are written texts in the poetry collection 'Before Alone' by M. Aan Mansyur, in the form of words, phrases, clauses, and sentences. The data source in this study is the poetry collection 'Before Alone' by M. Aan Mansyur, second edition: 2021, published by JBS Publisher, with 79 pages. The data collection technique in this study uses reading and note-taking techniques. The research is based on 30 analyzed data according to the objectives of this study, namely form, meaning, and function. This study yielded 11 data of anthropomorphic figure metaphors, 6 data of abstract to concrete metaphorical forms, and 13 data of synesthetic metaphorical forms found based on Parera's theory. The meaning of metaphorical figures in this study shows various perspectives. Through the analysis of Lakoff and Johnson's theory on metaphor, the research reveals the complexity of emotions, internal conflicts, and spiritual journeys of humans through the use of metaphorical language. Meanwhile, the functions of metaphorical figures in the poetry collection